Realistic behaviour simulation of a humanoid robot - Lima, José (2010)
This paper describes a humanoid robot simulator with realistic dynamics. As simulation is a powerful tool for speeding up the control software development, the proposed accurate simulator allows to fulfil this goal. The simulator is based on the Open Dynamics Engine and GLScene graphics library, providing instant visual feedback. User is able to test any control strategy without bringing damage to the real robot in the early stages of the development. The proposed simulator also captures some characteristics of the environment that are important and allows to test controllers without access to the real hardware. Experimental and simulator results are presented in order to validate the proposed simulator.